Class of Sturm–Liouville Problems with Eigenparameter Dependent Transmission Conditions. (3rd October 2017) - Aydemir, Kadriye; Mukhtarov, Oktay Sh.
ABSTRACT: The objective of this paper is the investigation of a new class Sturm–Liouville problems on two disjoint intervals when the eigenparameter appears not only in the equation but also in the boundary and transmission conditions. We concerned with the problem of justifying some spectral properties of the eigenvalues and corresponding eigenfunctions. Particularly, we examined asymptotic behavior of the eigenvalues and corresponding eigenfunctions.